2020
DOI: 10.1332/174426419x15468577044957
|View full text |Cite
|
Sign up to set email alerts
|

Collective knowledge brokering: the model and impact of an embedded team

Abstract: IntroductionThe Bristol Knowledge Mobilisation (KM) Team was an unusual collective brokering model, consisting of a multi-professional team of four managers and three academics embedded in both local healthcare policymaking (aka commissioning) and academic primary care. They aimed to encourage ‘research-informed commissioning’ and ‘commissioning-informed research’. This paper covers context, structure, processes, advantages, challenges and impact.<br /> Methods<br />Data sources from brokers includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
(79 reference statements)
1
25
0
Order By: Relevance
“…These observations reflect the nature of many of the early published examples of embedded research initiatives, which tend to comprise a lone researcher working outside their usual setting. While we found similar examples, we also identified more recent examples that comprised teams of embedded researchers (Crowe et al, 2017;Wye et al, 2019). Our workshop participants suggested that multidisciplinary embedded research teams, as well as having the potential to address the emotional and practical challenges facing individual embedded researchers, could make an important contribution to addressing the complex issues that face healthcare organisations.…”
Section: Scalesupporting
confidence: 72%
See 2 more Smart Citations
“…These observations reflect the nature of many of the early published examples of embedded research initiatives, which tend to comprise a lone researcher working outside their usual setting. While we found similar examples, we also identified more recent examples that comprised teams of embedded researchers (Crowe et al, 2017;Wye et al, 2019). Our workshop participants suggested that multidisciplinary embedded research teams, as well as having the potential to address the emotional and practical challenges facing individual embedded researchers, could make an important contribution to addressing the complex issues that face healthcare organisations.…”
Section: Scalesupporting
confidence: 72%
“…Once she was sitting in on this group, [initially] she couldn't figure out what she was going to do that was going to be helpful for them. (Embedded research manager, Battleford) Our data showed that there was a tendency for those leading initiatives to be overambitious about the activities that researchers should carry out, leading to 'role strain' and contributing to boundary management difficulties (Wye et al, 2019). Our interviewees and workshop participants suggested that focusing on the purpose of activities was an important way of combatting this.…”
Section: Functional Activitiesmentioning
confidence: 89%
See 1 more Smart Citation
“…networking events) to achieve this. As identified in previous research, knowledge sharing was based on trusting relationships [ 64 , 65 ], and provided SiREN with a valuable understanding of the system which it used to inform the development of its activities (e.g. research project topics, types of training offered).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent analysis of team brokering, Wye et al (2020) note that we need more comprehensive explanations for how knowledge brokers construct positive interactions and mediate across different institutions and levels of authority. It has been suggested that evaluations could be based on constructing a preliminary theory (Ward, 2017), also recommended in case-study method, which emphasises the importance of creating a preliminary logic model to measure progress (Yin, 2003) .…”
Section: Discussionmentioning
confidence: 99%